Topic-focused thread-based instant messenger - Ma, Weiming (2009)
An Instant Messenger (IM) is a popular network communication tool that allows a user to keep in touch with friends, families and colleagues both at home and in the workplace. IM applications are ubiquitous among today’s online communities, easily accessible on most computing platforms and mobile devices.